Percepción de la población sobre los puntos de acumulación de residuos sólidos municipales. carretera Iquitos – Nauta. San Juan Bautista. 2023 - Panduro Echevarria, Amy Marcela (2024)
The present research aimed to study the perception that the inhabitants have about the accumulation points of solid waste on the Iquitos - Nauta highway in 2023. The research, due to its approach, was quantitative, prospective, of a simple descriptive and comparative level, of non-experimental research design. The target population was made up of the residents living between km 1 to 8, in 2023. The sample was also made up of 67 residents who were present at the time of data collection, inclusion and exclusion criteria were taken into account, the technique used was the survey and the instrument applied was a 20-question questionnaire, which passed validity and reliability tests. The data obtained through the data collection instrument was analyzed considering the objectives and research hypothesis and later expressed in a Basic Data Matrix (BDM) and analyzed, processed and tabulated through the SPSS statistical package version 27. The main results expressed that there are predominantly unfavorable and very unfavorable physical and emotional perceptions regarding the presence of solid waste accumulation zones, and that it somehow remains according to gender and the level of instruction in these residents, so it is necessary that municipal institutions, whether district or provincial, take actions on this issue as it affects not only physically but also emotionally the residents settled along the Iquitos - Nauta highway.